Проектування системи надання доступу з використанням біометричних ознак - Осташук, Орест; Басюк, Тарас (Видавництво Львівської політехніки, 2017)
This article is devoted to designing the system of access control which uses biometric characteristics. Current approach provides the basis for creating authentication subsystem with user’s face as authenticator. The proposed system should also capture the images of the same object from different angles by using static digital camera. Possible approaches of selecting recognition and optimization algorithms for image processing are reviewed in this work.
Keywords: біометрія; автентифікація; афінні перетворення; шаблон